Para una hermenéutica de La Frontera (De La Escena Contemporánea) - Montenegro Sandoval, Fernando (2021)
Gloria Anzaldúa defines La Frontera as “an open wound where the Third World scratches the first and bleeds”. Borders are the product of diverse historical phenomena that Aníbal Quijano abbreviates with the term coloniality of power. Any theory of interpretation that chooses to approach the frontier must confront colonial difference. In the present work, the author grapples with the issue of interpretation when confronting La Frontera. His hypothesis is that the border demands a peculiar way of approaching the literary text. Doris Sommer understands this particular way as a form of “reading in a minor key”.